Carbon Nitride‐Supported Silver Nanoparticles: Microwave‐ Assisted Synthesis of Propargylamine and Oxidative C‐C Coupling Reaction. Issue 2 (9th January 2018) - Patel, Sunil B.; Vasava, Dilip V.
Abstract: In the present study we have, synthesized silver nanoparticles supported on carbon nitride AgNPs@g‐C3 N4 and investigated its catalytic aspects by using microwave. We found that silver nanoparticles supported on g‐C3 N4 were highly active in the A 3 ‐coupling reaction of (Aldehyde, secondary amine and terminal alkynes) for the synthesis of propargylamines with excellent yield up to 97% and in C−C coupling reaction of terminal alkynes for the synthesis of 1, 3‐diyne with excellent yield up to 98%. We have achieved excellent TON (72932), TOF (3636 min −1 ), E‐factor (0.27) and atom economy AE (94%). Reaction parameters like effect of catalyst quantity, effect of time and effect of temperature was deeply studied. The catalyst was characterized by SEM, HR‐TEM, EDX, XRD, ICP‐AES and IR. Abstract : An efficient, green and sustainable strategy for the oxidative C−C coupling reaction of terminal alkynes to produce a wide variety of 1, 3‐butadiyne and quick access of diverse propargylamine moieties using AgNPs@g‐C3 N4 heterogeneous catalyst under greener reaction conditions using [water :ethanol (4:1) ] solvent system and water is produced as the only side product in both the transformation.